Struktur Nalar Arab-Islam Menurut Abid al-Jabiri - M. Faisol (TSAQAFAH, 2010)
Al-Jabiri’s thought renewal project focuses on epistemological critics on scientific traditional framework of Arab-Islam. This is done by analyzing sociopolitical background of the formulation process and structure of Arab-Islam’s logical reasoning, and the entire structural working mechanism of Arab’s logical reasoning. According to Al-Jabiri, Arab’s logical reasoning can be classified into three, i.e. bayani, Irfani and burhani. Bayani is a pure Arab’s logical reasoning as it is motivated by cognitive factor to interpret religious texts. Irfani becomes an alternative epistemology for bayani in providing convincing conclusions. While Burhani, is logical reasoning based on rationality. However, even though the Arab’s logical reasoning could be distinguished into those three, Al-Jabiri observes the domination of bayani on others, thus, the text and traditional authorities are always dominating Arab-Islam civilization. Consequently, Arabic Civilization is not creative-productive or poor in concepts and theories. The solution AlJabiri proposes is to apply critism spirit that have been developed in AndalusiaMaghrib, i.e. empirical rationale presented by Ibn Hazm and Al-Syatibi in Fiqh, Ibnu Ruysd in Philosophy, Ibnu Khaldun in sociology, and Ibn Madha alQurthubi in Arabic grammatical renewal.